The Resilience of Non-Sharia Compliant Company in Indonesia Stock Exchange (IDX) and its Determinants: Evidence from 2005-2013 - Qizam, Ibnu; Ardiansyah, Misnen; Qoyum, Abdul (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
The aims of this study were to examine the resilience of non-sharia stock in Indonesia, to measure the impact of macro-economic variables and micro-company specific factors toward resilience. All the data, including 30 non-sharia companies in Indonesia, are retrieved from Indonesia Stock Exchange and Bloomberg database. Our dataset spans from 2005 to 2013, the study employs GMM Estimation Approach to estimate the determinants of companyâ€™s resilience in Indonesia. The results find that profitability ratios (ROE, ROIC, NIM), liquidity ratio (CASHR, CURR), debt asset ratio, and lagged dependent variable (Mertonit-1) are found to be statistically significant determinants of Merton distance-to-default. The company size is not a good predictor of the default risk for companies observed. This study emphasizes the benefits of using several accounting-based measures in company-default prediction models.Â